Analisis Kebutuhan Pengembangan Perangkat Lunak Pada Pembelajaran Bahasa Inggris untuk Mengatasi Masalah Pelafalan - Faathir Faathir; Sulthoni Sulthoni; Henry Praherdhiono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
This study aims to examine the needs of EFL learners in Indonesia towards Pronunciation as a focus point of the development of English pronunciation learning software. This research uses descriptive analysis which analyzes and observes previous studies regarding the pronunciation problems experienced by students from various regions in Indonesia. The literature review shows that there are still many pronunciation errors that are often associated with the absence of an English sound in their mother tongue. This has also emerged several patterns of errors experienced by students. The result deduces that EFL learners need the supporting software to cope with the pronunciation problems that can describe the potential pronunciation errors and segmental aspect of each English sound.